PLA2R1 and HLA-DQA1 SNP in patients with primary membranous nephropathy - Junyi Zhou; Zhijian Zhang; Kezhi Zhou; Leting Zhou; Jing Xue; Bin Liu; Xiran Zhang; Ting Cai; Biao Huang; Yi Zhang; Zhigang Hu; Liang Wang; et al. (PLoS ONE, 2025)
Background Primary membranous nephropathy is a widely recognized autoimmune disease associated with podocyte antigens; the most important autoantigen is PLA2R1. PLA2R1 and HLA-DQA1 play important roles in the production of pathogenic antibodies. The purpose of this study was to observe the relationship between gene polymorphisms and primary membranous nephropathy and explore the clinical functional clues of PLA2R1 and HLA-DQA1 genes affecting treatment responsiveness. Method The study enrolled 89 patients with primary membranous nephropathy and 91 healthy people as a control. Single-nucleotide polymorphism loci (seven on PLA2R1 and two on HLA-DQA1) were identified using the PCR-Sanger technique. The patients were followed up until the 12th month, and relevant clinical data were collected. The relationship between these single-nucleotide polymorphism loci and primary membranous nephropathy remission was analyzed. Result Genotypic and allelic frequency distributions for six single-nucleotide polymorphisms within PLA2R1 (rs4664308, rs3792189, rs3792192, rs1870102, rs17831251, and rs35771982) and one in HLA-DQA1 (rs2187668) were associated with morbidity of primary membranous nephropathy. Single-nucleotide polymorphisms rs1870102, rs17831251, and rs2187668 were statistically significant in the genetic model analysis. The odds ratio for primary membranous nephropathy in patients carrying rs2187668 GG and rs1870102 AA was 52.875. We found that PLA2R1 single-nucleotide polymorphism rs36771982 was related to proteinuria remission at the 12th month, and found in further analysis that PLA2R1 single-nucleotide polymorphisms rs3792189, rs3792192, rs17831251, and rs35771982 were related to treatment response in the RTX group. Conclusion In this study, we found several PLA2R1 and HLA-DQA1 single-nucleotide polymorphism loci associated with primary membranous nephropathy morbidity and that some PLA2R1 single-nucleotide polymorphism loci were related to the treatment response of patients with primary membranous nephropathy.